Sozioökonomische Bildung – ein Exempel für das Verhältnis von Disziplinarität und Transdisziplinarität; Socioeconomic education – an example of the relationship between disciplinarity and transdisciplinarity - Reinhold Hedtke (Bielefeld University, 2023)
Die Beiträge diskutieren die Belastbarkeit der Prinzipien Disziplinarität und Transdisziplinarität am Exempel der sozio|ökonomischen Bildung als Teil der sozialwissenschaftlichen Domäne der Schule. Vier Fragestellungen stehen im Zentrum: Was spricht für das Disziplinaritätsprinzip in der sozialwissenschaftlichen Domäne und der sozio| ökonomischen Bildung? Hilft das Kriterium Disziplinarität dabei, Bildungen und Schulfächer sinnvoll zu ordnen? Was leistet es für die curricular- inhaltliche Konstruktion von Schulfächern und für ihre Kooperation? Eignet sich wissenschaftliche Multiperspektivität als Leitprinzip für Schulfächer und Curricula allgemeinbildender Schulen? – – The contributions discuss the validity of the principles of disciplinarity and transdisciplinarity using the example of socio|economic education as part of the social science domain of schools. Four questions are at the centre: What arguments are there in favour of the principle of disciplinarity in the social science domain and in socio|economic education? Does the criterion of disciplinarity help to organise education and school subjects in a meaningful way? What can it contribute to the construction of school subjects in terms of curricula and content and to their cooperation? Is scholarly multiperspectivity suitable as a guiding principle for school subjects and curricula of general education schools?
Keywords: A12; A20; 330; ökonomische Bildung; economic education; Schulfach; school subject; Disziplinarität; disciplinarity; Transdisziplinarität; transdisciplinarity